Preparation and properties of carboxylated cellulose nanofibers/monomer casting nylon composites. Issue 10 (1st September 2022) - He, Xiaofeng; Guo, Fuqiang; Ge, Tiejun; Tang, Kaihong; Shi, Shengnan; Geng, Maofu
Abstract: Polyisocyanate was used to chemically functionalize carboxylated cellulose nanofibers (CNF‐C). Composites of CNF‐C/ monomer casting nylon (MC nylon) and modified CNF‐C/MC nylon were fabricated by anionic ring‐opening polymerization. The mechanical characteristics of the MC nylon composites and the dispersion of the CNF‐C in the MC nylon were studied. The tensile strength and impact strength of composites were first increased with CNF‐C addition, but then decreased as further CNF‐C was added. The composites had good mechanical properties when CNF‐C was added to MC nylon at 1.0 wt%, and the tensile strength and impact strength were increased by 21.2% and 34.9%, respectively, compared to MC nylon. When modified CNF‐C was added at 1.5 wt%, the tensile strength of composites was increased by 47.90%. The addition of CNF‐C causes an increase in the melting point, crystallinity, and crystallization temperature, which was confirmed by differential scanning calorimetry (DSC). The modified CNF‐C had better dispersibility in MC nylon which was confirmed by scanning electron microscopy (SEM). Abstract : In order to improve the mechanical properties of MC nylon, CNF‐C/MC nylon composites were prepared. The tensile strength and impact strength of MC nylon were increased with CNF‐C adding. After the addition of the modified CNF‐C, the tensile strength of the composite material is increased again, mainly because CNF‐C will agglomerate in MC nylon, and the modified CNF‐C is better dispersed in MC nylon.